Replacement names for three preoccupied genus-group names of Cetoniinae (Coleoptera: Scarabaeidae) - Allsopp, Peter G.; Jákl, Stanislav; Rey, Antonio (Zootaxa, 2023)
The names of three genus-level taxa of Cetoniinae from Southeast Asia are reviewed. Aurelia Thomson, 1880, currently a subgenus of Ixorida Thomson, 1880, is preoccupied by Aurelia Lamarck, 1816, and Emas Allsopp, Jákl & Rey, new replacement name, is proposed. This results in Ixorida (Emas) decorata Antoine, 1986, Ixorida (Emas) gloriosa Jákl, 2014, Ixorida (Emas) kaorui Jákl, 2019, Ixorida (Emas) philippei Sakai & Nagai, 1998, and Ixorida (Emas) thoracica (Wallace, 1867). Legrandia Jákl, 2019, currently a subgenus of Ruteraetia Krikken, 1980, is preoccupied by Legrandia Beddome, 1883, and Legrandetia Allsopp, Jákl & Rey, new replacement name is proposed, resulting in Ruteraetia (Legrandetia) pahangensis Jákl, 2019. Sternoplus Wallace, 1867 is preoccupied by Sternoplus Mulsant & Rey, 1864, and Walsternoplus Allsopp, Jákl & Rey, new replacement name is proposed, resulting in Walsternoplus schaumii (White, 1856), new combination, and Walsternoplus chicheryi (Antoine, 1999), new combination.